Effects of prevention and harm reduction interventions on gambling behaviours and gambling related harm: An umbrella review. (March 2019) - McMahon, Naoimh; Thomson, Katie; Kaner, Eileen; Bambra, Clare
Abstract: Background: Harms related to gambling have been found not only to affect problem gamblers, but also to occur amongst low- and moderate-risk gamblers. This has resulted in calls for a public health approach to address a possible 'prevention paradox' in gambling related harm. The aim of this study was to evaluate the systematic review evidence base on the effects of prevention and harm reduction interventions on gambling behaviours, and gambling related harm. We also aimed to examine differential effects of interventions across socio-demographic groups. Methods: Systematic methods were used to locate and evaluate published systematic reviews of prevention and harm reduction interventions. We designed the review using the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) Equity extension Guidelines. Four databases were searched from their start date until May 2018. The quality of the included articles was determined using A MeaSurement Tool to Assess systematic Reviews (AMSTAR 2). Results: Ten systematic reviews were identified reporting 55 unique relevant primary studies. Much of the review evidence-base related to pre-commitment and limit setting (24%), self-exclusion (20%), youth prevention programmes (20%), and machine messages/feedback (20%). The effectiveness of harm reduction interventions are limited by the extent to which users adhere to voluntary systems. Less than half of studies examining youth prevention programmes demonstrated positive effects on behaviour. No review extracted data or reported on the differential effects of intervention strategies across sociodemographic groups. The quality of the included reviews (and their primary studies) were generally poor and clear gaps in the evidence base have been highlighted. Conclusions: The evidence base is dominated by evaluations of individual-level harm reduction interventions, with a paucity of research on supply reduction interventions. Review conclusions are limited by the quality and robustness of the primary research. Future research should consider the equity effects of intervention strategies. Highlights: First umbrella review evaluating the effectives of prevention and harm reduction interventions on gambling behaviour. Found evidence of 10 reviews reporting 55 unique primary studies. Evidence relates mostly to pre-commitment/limit setting, self-exclusion, youth prevention programmes and messages/feedback. Review-level evidence is poor, and no review reported differential effects of interventions across sociodemographic groups.